A cystic, septated lesion in the liver with unusual diagnosis. (28th October 2014) - van Seventer, Iteke; Verheij, Joanne; Phoa, Saffire; van Gulik, Thomas M
Abstract : A 51-year-old male patient from Iraq presented with symptoms of right upper-quadrant abdominal pain. Imaging showed a 9 cm, lobulated cystic lesion in the right liver lobe with thin septations, suggestive of a hydatid cyst. Although serology for hydatid disease was negative, the cystic lesion was treated by percutaneous drainage. Owing to persisting symptoms, he was re-evaluated showing the same cystic lesion unchanged. On the presumptive diagnosis of a cystadenoma or cystadenocarcinoma, patient underwent laparotomy. A solitary, cystic lesion was found that was removed by local excision. Macroscopical examination revealed a multilocular, septated tumour. Histopathological assessment showed lining of the cysts with epithelioid cells that showed immunohistochemical features consistent with a mesothelial origin; the pathology findings are consistent with an adenomatid tumour; in the differential diagnosis a benign multicystic mesthelioma was also considered. These are rare cystic lesions in the liver of which only few cases have been described in literature.